The role of the hidden curriculum in enhancing intellectual security in Saudi education from the point of view of students of the third secondary students and the reasons for its weakness from the point of view of teachers - Al-Enezi, Nouf Atallah; Al-Rashidi, Sarah Mohammed; Al-Anzi, Ataf Lahiq (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the role of the hidden curriculum in enhancing intellectual security in Saudi education from the point of view of students of the third secondary students, and the reasons for its weakness from the point of view of teachers, and to reveal the impact of the gender variable on the views of the sample of the two categories, The researchers used the descriptive survey method, and the tool was a questionnaire From (63) statements, divided into two axes, was distributed to a simple random sample consisting of (2190 respondents), including (1400) students and (790) teachers, The results showed that the hidden curriculum contributes to enhancing intellectual security in Saudi education with a total average of (3.51 out of 5), that is, to a large extent. At the level of the sub-components, the cultural background and the level of the teacher’s performance got the highest average (3.99), then the learner’s cultural background (3.61). School benefits (3.59), fourth, the textbook, with an average of (3.55), all of them with a (significant) degree, fifthly, the study schedule, with an average of (3.18), and finally the arrangement of the classroom and the placement of furniture (3.16), and the latter two with a (average) degree, and there are differences between the points of view of the sample according to the gender variable in The degree of the hidden curriculum’s contribution to enhancing intellectual security for the benefit of male students, Based on the results, the researchers recommended qualifying human resources in education with specialized qualification in intellectual security and developing teacher nomination procedures to include tests of intellectual and behavioral attitudes before appointment as a preventive measure, and after appointment as a remedial measure, and proposes studies on the role of education in consolidating intellectual security, and programs to develop the concept of the hidden curriculum.